Understanding youth athlete motivation, training and activity progression during and after the COVID-19 sports interruption - Lawrence, J. T.; Greenberg, E.; Greenberg, E.; Ganley, T. J. (Pediatrics, 2022)
Background: COVID-19 restrictions created a period of disrupted sports participation for youth athletes. The physical conditioning and sports training habits of youth athletes during COVID-related sports interruption and upon returning to normal sports activity are currently unknown. The purpose of this study was to determine the extent to which athletes maintained their training levels during the COVID-19 pandemic and understand the strategies that enhanced motivation and adherence to a training regimen while in isolation. A secondary aim was to further understand the manner as to how youth athletes returned to activity and identify any secondary effects of the prolonged sports interruption as they resumed athletic activities. Methods: A two-part survey was designed to determine activity changes, type of organized instruction, and athlete preferences for training support. This was distributed by email using snowball sampling methodology to athletes 14-21 years-old who were involved in competitive sports when pandemic restrictions were enacted. As sports activities resumed, a follow-up survey was distributed to the same respondents to identify feelings of preparedness, training habits, and injuries. This study was reviewed and approved by the Institutional Review Board of the sponsoring organization. Results: Of the 155 subjects (mean age 16.1 ± 2 years, 64.5% female) that completed the initial survey, 98% reported a stoppage of in-person sports participation and 70% decreased their exercise/training volume, with 41% (n=63) reporting > 50% reduction. Most athletes (86%) received instruction from coaches, with written workouts (70%) being most common, however most athletes (70%) preferred instructor-led, group training sessions. Many athletes (73%) reported supplementing team-based training recommendations with independent workouts, primarily jogging (62%), strength training (54%) and sports specific skills (51%). With regards to their feelings of preparedness for returning to normal sports activity, 42% of athletes reported feeling only minimally or somewhat prepared. Of the 43 subjects that completed the follow up survey (34% response rate), 30% reported immediately returning to play for more than one team, and there was a sharp increase in athletic exposures compared to mid-pandemic levels (Figure 1). Despite this increase in structured athletic activity, 63% of the sample reported they still supplemented team-based practices with jogging (51%), sports specific skill work (47%) and strength training (40%) on an individual basis. Interestingly, 25% of athletes reported sustaining a sports-related injury a mean of 79 days after resuming sports activities. Conclusion: Pandemic-related sports restrictions resulted in a large reduction in youth athlete training and conditioning. Coaches attempted to maintain training via use of written workouts, however athletes preferred instructor-led, group training sessions. There was a rapid resumption of sports activities, which may have contributed to the high rate of injuries seen in this study.